Respostas

A melhor resposta!
2014-07-13T14:26:50-03:00
F)  a1= 2
  r= 2

an= a1 + (n-1) r

an = 2 + (n-1) 2
an= 2 + 2n -2
an= 2n
                  (a1 + an )n               (2 + 2n ) n            2n +  2n²
        Sn = ----------------        = -----------------     =  ---------------
                         2                                   2                           2

Sn = n² + n

G )   a1 = n-5

r= (n-1)  - (n-5) = 4

an= a1 + ( n-1) r

an = (n-5) +(n-1)4 = 5n - 9

Sn = (a1 + an) n
      ------------------
                  2
      (n-5) + ( 5n - 9) n          (6n-14) n
Sn =---------------------  =   ----------------- =  3n² -7n
                    2                               2

1 5 1